PERJANJIAN BANGUN GUNA SERAH (BUILD, OPERATE AND TRANSFER) ANTARA PEMERINTAH PROVINSI SUMATERA SELATAN DENGAN PIHAK SWASTA - Justisia, Vita (Nurani, 2015)
Abstract: The availability of adequate infrastructure, need tosupport the implementation of national development and toimprove Indonesia's competitiveness in the global era. Toovercome this, the Government of South Sumatra Province tobuild agreement Build, Operate, and Transfer in thedevelopment of infrastructure without burdening the localbudget through cooperation with Third Parties. This article willbe assessed on what consideration the Government of SouthSumatra Province in determining system Build, Operate, andTransfer, procedures and implementation agreements totransfer wake, as well as whether to transfer the wakeagreement meets the principle of balance and legal certainityimproving the welfare of society.ملخص: توافر البنیة التحتیة المناسبة، حاجة ملحة لدعم تنفیذ التنمیة الوطنیةوتحسین القدرة التنافسیة اندونیسیا في عصر العولمة. للتغلب على ھذه، وحكومةمقاطعة سومطرة الجنوبیة لبناء اتفاق تطبیق سارح في تطویر البنیة التحتیة دونإثقال كاھل المیزانیة المحلیة من خلال التعاون مع الأطراف الثالثة. في ھذه الدراسةسیتم تقییمھا على ما نظر حكومة مقاطعة سومطرة الجنوبیة في نظام تحدید البناءوصولا إلى سارح وإجراءات و اتفاقات التنفیذ لنقل بعد، وكذلك ما إذا كان سیتم نقلالاتفاق أعقاب یلبي مبدأ التوازن و الیقین القانوني في تحسین رفاھیة المجتمع.Kata Kunci: Perjanjian Bangun Guna Serah